What do patients with substance use disorders know about their medication? A cross-sectional interview-based study - Heck, Johannes; Dubaschewski, Melanie; Krause, Olaf; Bleich, Stefan; Schulze Westhoff, Martin; Krichevsky, Benjamin; Glahn, Alexander; Schröder, Sebastian (Frontiers in Psychiatry, 2025)
PurposeThis study investigates the medication knowledge of patients with substance use disorders (SUDs) treated at a psychiatric clinic in northern Germany, aiming to identify gaps in understanding and to enhance patient safety, particularly concerning ATC group A drugs.SettingThe study was conducted in the Department of Psychiatry, Social Psychiatry, and Psychotherapy at Hannover Medical School, Germany.DesignA cross-sectional, interview-based study using a convenience sample of 100 patients was conducted between March 2023 and April 2024.ParticipantsThe cohort included patients with SUDs who had been hospitalized for at least 72 hours, regularly took at least one medication in addition to withdrawal drugs, and who displayed no cognitive impairments. Participants had a median age of 46.5 years; 62% were male.InterventionPatients were interviewed using a customized questionnaire addressing knowledge of drug name, indication, dosage, and frequency of application. The questionnaire also assessed the sources of medication knowledge and patient opinions on their medication regimen.Primary and secondary outcome measuresThe primary outcome was the average medication knowledge score (range 0–6). Secondary measures included differences in knowledge across drug groups, sources of information, and demographic influences.ResultsThe median medication knowledge score was 3.8 out of 6. Knowledge was significantly lower for ATC group A drugs compared to groups B, C, and N (p < 0.001). No significant differences were observed between men and women nor between age groups. Hospital physicians were the primary information source for 40% of patients. Most participants (84%) considered their medication regimen adequate.ConclusionPatients with SUDs demonstrated suboptimal medication knowledge, particularly regarding ATC group A drugs. Future strategies should prioritize patient education and enhanced physician engagement to improve understanding and adherence, ultimately fostering better therapeutic outcomes.